The use of isoluminant stimuli to identify the role of the magnocellular pathway in written word recognition - Tonkin, Richard Pearce (2005)
Previous research has indicated that information carried by the Magnocellular (M) pathway may be used in written word recognition and reading, although these findings are far from conclusive. The precise nature of this potential role of the M pathway in word recognition is also unclear, with some researchers suggesting that it is to convey word-level shape information whilst other researchers have indicated that the M pathway’s role may relate to attentional selection. Eight experiments are reported that used isoluminant stimuli to investigate the validity of these claims. Experiment 1 examined the use of Heterochromatic Flicker Photometry to create isoluminant stimuli and in particular, the effect of stimulus type on the luminance ratios obtained. Experiments 2-4 investigated the recognition of words, pseudowords and illegal nonwords under isoluminant and non-isoluminant conditions in a Reicher-Wheeler task. Experiment 5 was a further Reicher-Wheeler task experiment in which case type (lowercase, UPPERCASE, and MiXeDcAsE), stimulus type and target luminance were varied. The recognition of isoluminant and non-isoluminant letter and nonletter strings were compared in Experiments 6 and 7. Experiment 8 used a similar design to previous experiments to investigate whether the recognition of isolated letters might also use M pathway information. These experiments revealed that with lowercase words, accuracy in the Reicher-Wheeler task is reduced at isoluminance in comparison to perception under non-isoluminant conditions, indicating that M pathway information is used in the recognition of these stimuli. Furthermore, this reduction in accuracy at isoluminance was shown to extend to pseudowords and illegal nonwords, to words and nonwords presented in upper and mixed case, and to isolated letters. However, with nonletter strings, no reduction in accuracy at isoluminance was obtained in the Reicher-Wheeler task. The implications of these findings for the various theoretical explanations of the M pathway’s role in written word recognition are discussed.